The empirical determinants of the Euro: Short and long run perspectives - Menzie David Chinn (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The behavior of the dollar/euro exchange rate is modeled using a monetary model of the exchange rate. The econometric analysis is complicated by the short sample span of actual euro data available for analysis. Hence, data on a synthetic euro are used. The assumptions underlying the monetary approach are discussed. A cointegrating relationship involving the exchange rate, money stocks, industrial production, interest and inflation rates, augmented by a relative price of nontradables, is identified for the 1991M08-1999M12 period using the Johansen procedure. The model implies that the euro was undervalued by about 13-15% in January 2000. This finding is robust to the use of alternative sample periods, and alternative estimation methodologies such as single-equation error correction and first differences specifications. A longer term perspective is provided by a productivity-based model of the real value of the euro. Some panel regression estimates of the relationship between intercountry relative productivity differentials and real exchange rates is presented. Using these estimates to conduct some calculations, one comes to the conclusion that unless drastic changes to productivity trends occur, there is little reason to believe that the real value of the euro will deviate from its current zero-drift path.
urn:nbn:de:kobv:11-10047552
Keywords: F31; F41; F47; 330; euro; exchange rate; monetary model; productivity